2016
DOI: 10.1128/jvi.00119-16
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Analyses of Swine Major Histocompatibility Complex Class I Complexes and Prediction of the Epitope Map of Important Influenza A Virus Strains

Abstract: The lack of a peptide-swine leukocyte antigen class I (pSLA I) complex structure presents difficulties for the study of swine cytotoxic T lymphocyte (CTL) immunity and molecule vaccine development to eliminate important swine viral diseases, such as influenza A virus (IAV). Here, after cloning and comparing 28 SLA I allelic genes from Chinese Heishan pigs, pSLA-3*hs0202 was crystalized and solved. SLA-3*hs0202 binding with s␤2m and a KMNTQFTAV (hemagglutinin [HA]-KMN9) peptide from the 2009 pandemic swine H1N1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 64 publications
2
35
0
Order By: Relevance
“…However, in terms of peptide binding, the SLA-1 * 1502 structure not only reflects the common features of SLA-I alleles but also exhibits unique allelic-specific characteristics. Similar to the previously resolved SLA-1 * 0401 and SLA-3 * hs0202, the N-terminus of the SLA-1 * 1502 PBG is open because the amino acid at position 167 of the A pocket is a small Ser (Figure 2A), but in other species such as humans and mice, the amino acid at this position is a large Trp (19,20). The peptide-binding motif of SLA-1 * 1502, like that of SLA-1 * 0401 FIGURE 6 | Peptide predictions from different PRRSV strains according to the binding motifs of the pSLA-1*1502 complex.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…However, in terms of peptide binding, the SLA-1 * 1502 structure not only reflects the common features of SLA-I alleles but also exhibits unique allelic-specific characteristics. Similar to the previously resolved SLA-1 * 0401 and SLA-3 * hs0202, the N-terminus of the SLA-1 * 1502 PBG is open because the amino acid at position 167 of the A pocket is a small Ser (Figure 2A), but in other species such as humans and mice, the amino acid at this position is a large Trp (19,20). The peptide-binding motif of SLA-1 * 1502, like that of SLA-1 * 0401 FIGURE 6 | Peptide predictions from different PRRSV strains according to the binding motifs of the pSLA-1*1502 complex.…”
Section: Discussionsupporting
confidence: 75%
“…The amino acid compositions of these three pockets in SLA-1 * 1502 are shown in Figures 2C-E. No hydrogen bonds or salt bridges were found in these structures; instead, many VDWs were observed between the three pockets and the NSP9-TMP9 peptide ( Table 3). The D pocket is critical for the peptide selection of SLA-1 * 0401 and SLA-3 * hs0202 because of the charged residue at position 156 (19,20). The non-polar Met 156 causes the D pocket of SLA-1 * 1502 to be hydrophobic, in contrast to the charged D pocket of SLA-1 * 0401 or SLA-3 * hs0202 (Figure 3).…”
Section: Prrsv Peptide Prediction and Verification Of Sla-1 * 1502mentioning
confidence: 99%
See 2 more Smart Citations
“…The employed approach was justified by 1) the high degree of structural similarity and identification of cross-species influenza virus cytotoxic T lymphocytes epitopes between HLA and SLA class I molecules (Zhang et al, 2011), 2) phylogenetic analyses that demonstrated strong sequence homology between SLA and HLA class II genes (Smith et al, 2005), and 3) previously reported swine epitope prediction studies (Burgara-Estrella et al, 2013; Díaz et al, 2009;Zimic et al, 2011). Recent advancements associated with swine epitope prediction have been reported (Fan et al, 2016;Gutiérrez et al, 2016Gutiérrez et al, , 2015 and these expanded immunoinformatics knowledge and improved tools may result in better prediction of ASFV SLA epitopes for future analysis.…”
Section: Discussionmentioning
confidence: 99%